Resoluções de equações polinomiais e a insolubilidade da quíntica - Silva, Juliana Débora da [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Esta dissertação tem como objetivo explorar a história e os métodos de resoluções possíveis para equações de grau igual ou menor que cinco e tratar da impossibilidade de resolução por meio de radicais de equações gerais de grau igual a cinco. Para isso, serão explorados conceitos algébricos pertencentes à Teoria de Galois.

This dissertation aims to explore the history and potential methods of solving equations of a degree equal to or less than five. It also addresses the impossibility of solving these equations using general radical expressions with a degree of five. To achieve these objectives, the dissertation will delve into algebraic concepts within the Galois Theory.
Resolutions of polynomial equations and the insolubility of the quintic
Keywords: Álgebra; Equação; História da matemática; Resolução por radicais; Teoria de Galois; Algebra; Equation; Mathematics history; Radical resolution; Galois theory